POLITIK LUAR NEGERI INDONESIA TERHADAP TIONGKOK DALAM SENGKETA KEPEMILIKAN LAUT CINA SELATAN TAHUN 2012-2016 - Usman, Ricky; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe the foreign policy of Indonesia toward Tiongkok dominations in conflict at the South China Sea in 2012-2016. South China Sea are one of high seas in the world that have big potency in transportations, natural resources and economic interest. South China Sea are located in South East Asia region and have border with six countries such as Indonesia, malaysia, Filiphina, Vietnam, brunei Darussalam and China. Since 1972 China have a claim about the South China Sea and its make a conflict between China and the member of ASEAN.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the foreign policy of Indonesia toward Tiongkok dominations in conflict at the South China Sea. The theories applied in this research are realisme perspective with national interest concept.The result shows that foreign policy of Indonesia toward Tiongkok dominations in conflict at the South China Sea are Indonesia have a use peacefull diplomacy in conflict in South China Sea, Indonesia Government use a non intervence proncipall, Indonesia use affirmations guidline Code of Conduct and Declaration on the Conduct (DOC) of Parties in the South Tiongkok Sea and Indonesia have a potimalization Asean Regional Forum roles in conflict South China Seas.Key words: policy, conflict, Diplomacy and South China Sea